Pengaruh Kegiatan Literasi di Pagi Hari Terhadap Peningkatan Minat Belajar Mata Pelajaran IPS Terpadu Bagi Siswa Kelas VII di SMP Negeri 1 Nangaroro - Esron Samba Pulu; Yosef Moan Banda (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2024)
This study aims to determine (1) Literacy learning activities of class VII students at SMP Negeri 1 Nangaroro. (2) Learning interests of class VII students at SMP Negeri 1 Nangaroro. The type of research is quantitative with a quantitative descriptive approach, the sample in this study was 43 respondents. Data collection techniques in the form of Observation, Questionnaires and Documentation. data analysis is linear regression. The results of data analysis and discussion show that the t_count> t_table value is 8.606> 2.202 and significant 0.000 <0.05. This shows that there is a significant influence between the literacy variable (X) on student learning interest (Y).